2023
DOI: 10.1136/ijgc-2022-003940
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus independent status on pathologic response and outcomes in locally advanced cervical cancer managed with chemoradiotherapy followed by surgery

Abstract: ObjectiveWhile human papillomavirus (HPV) has been shown to play a significant role in cervical cancer carcinogenesis (HPV associated cases), a considerable percentage of cervical cancers occur independently of HPV status (HPV independent).MethodsIn this retrospective study of 254 locally advanced cervical cancer patients treated with chemoradiotherapy and radical surgery, HPV genotypes were determined using the Anyplex II HPV28 kit that uses multiplex, real time polymerase chain reaction technology. The prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 33 publications
(65 reference statements)
0
11
2
Order By: Relevance
“…To date, treatment of both HPVA and HPVI SCCs is similar across international guidelines, including the 2023 National Comprehensive Cancer Network (NCCN) and the European Society of Radiotherapy and Oncology/European Society of Gynaecological Oncology (ESTRO/ESGO) guidelines. However, evidence indicates HPVI tumors do not respond to conventional oncologic therapy (complete response to chemo- and radiotherapy is much lower in HPVI tumors compared with HPVA tumors), and thus additional studies will be beneficial to develop alternative management options 17 . Turco et al[17] suggested that HPV status should be assessed at initial diagnosis, but this would require extensive and mostly unnecessary testing.…”
Section: Human Papillomavirus-independent Squamous Cell Carcinomasmentioning
confidence: 99%
See 3 more Smart Citations
“…To date, treatment of both HPVA and HPVI SCCs is similar across international guidelines, including the 2023 National Comprehensive Cancer Network (NCCN) and the European Society of Radiotherapy and Oncology/European Society of Gynaecological Oncology (ESTRO/ESGO) guidelines. However, evidence indicates HPVI tumors do not respond to conventional oncologic therapy (complete response to chemo- and radiotherapy is much lower in HPVI tumors compared with HPVA tumors), and thus additional studies will be beneficial to develop alternative management options 17 . Turco et al[17] suggested that HPV status should be assessed at initial diagnosis, but this would require extensive and mostly unnecessary testing.…”
Section: Human Papillomavirus-independent Squamous Cell Carcinomasmentioning
confidence: 99%
“…However, evidence indicates HPVI tumors do not respond to conventional oncologic therapy (complete response to chemo-and radiotherapy is much lower in HPVI tumors compared with HPVA tumors), and thus additional studies will be beneficial to develop alternative management options. 17 Turco et al [17] suggested that HPV status should be assessed at initial diagnosis, but this would require extensive and mostly unnecessary testing.…”
Section: Reproducibility Of Different Growth Patterns (Original Vs Co...mentioning
confidence: 99%
See 2 more Smart Citations
“…In the 2020 WHO classification, cervical SCCs are distinguished by HPVA versus HPVI status 12 . In cervical SCCs, however, HPVI tumors are rare and consequently difficult to study 20–22 . Estimates of the frequency of HPVI tumors vary widely, ranging from 0.23% to 9.09% of total cases depending on the cohort studied and HPV detection methods used 3,7,21–33 .…”
mentioning
confidence: 99%